Współczesne filozoficzne interpretacje psychoanalizy Sigmunda Freuda. Przegląd wybranych stanowisk - Szmaglińska, Katarzyna (Folia Philosophica, 2018)
The  author  of  the  paper  discusses  three  of  contemporary  interpretations  ofFreud’s psychoanalysis. Most recent interpretations go beyond one-sidedness of pre-vious ones (that is, biologism and hermeneutics) which took theory and practice sep-arately.  Thanks  to  reconstruction  of  some  of  philosophical  consequences  of  Freud’sthought — ontological (anthropological), epistemological and ethical — psychoanaly-sis  might  be  taken  as  metaphysical  concept  (Andrzej  Leder),  moral  philosophy(Alfred  I.  Tauber)  or  it  might  be  interpreted  dialectically  (Jon  Mills).  The  authorpoints  out  some  key  elements  of  Freud’s  theory,  which  make  these  interpretationspossible, and in this way she highlights validity of Freud and vivid reception of histhought in philosophy.